The relationship between emotional intelligence and work attitude: an examination among employees at Al-Ikhsan Sports Sdn. Bhd. / Sharifah Noor Shuhada Tuan Sidi - Tuan Sidi, Sharifah Noor Shuhada (2014)
This research is making to find the relationship of emotional intelligence towards work attitude among employees at Al-Ikhsan Sports Sdn Bhd. The research is making when the researcher find out that the employees at Al-Ikhsan Sports Sdn Bhd as a retailer company have the attitude problems such as absenteeism and turnover. The researcher also found the journals that reinforce the research that retailer companies always have the work attitude problem such as turnover and absenteeism. There are two research objectives and two research questions in this research that needed the researcher to find the relationship of the emotional intelligence toward work attitudes and the most influence factor of emotional intelligence toward the work attitudes. The work attitude as a dependent variable and three competencies of emotional intelligence that are self awareness, social awareness and self management are found out. The researcher is use the probability sampling that is simple random sampling as a sample technique. The population that is making is focused on male and female employees at Al-Ikhsan Sports Sdn. Bhd. The researcher is making the ranking for the total of a finding. The ranking is based on the result of reliability analysis, descriptive statistic, pearson correlation and coefficient of regression. The researcher found that self management is on the first ranking followed by self awareness and social awareness. The most influential factor that are been found out by this research is self management. The researcher also makes some recommendation for the future researcher and the management of the company.